O átomo de hidrogênio em 1, 2 e 3 dimensões - Verri, Alessandra Aparecida (Universidade Federal de São Carlos, 2007)
In this work we study the Hamiltonian of the hydrogen atom in 1, 2 and 3 dimensions. Especifically, it is defined as a self-adjoint operator in the Hilbert space L2(Rn), n = 1, 2, 3. Nevertheless, the main goal is to study the hydrogen atom 1-D. Particularly, for this is model we address some problens related to the singularity of the Coulomb potential.
Keywords: Teoria espectral (Matemática); Átomo de hidrogênio; Operadores auto-adjuntos; Coulomb, Potencial de; Hydrogen atom; Self-adjoint operator; Coulomb po- tential; CIENCIAS EXATAS E DA TERRA::MATEMATICA